2013
DOI: 10.1007/s00264-013-2095-y
|View full text |Cite
|
Sign up to set email alerts
|

Anterior decompression with single segmental spinal interbody fusion for Denis type B thoracolumbar burst fracture: a midterm follow-up study

Abstract: Purpose Our goal was to observe the midterm results of a case series of Denis type B thoracolumbar burst fracture treated with anterior decompression with single segmental spinal Interbody fusion. Methods Twenty patients with Denis type B thoracolumbar burst fractures underwent anterior decompression with single segmental spinal Interbody fusion. They underwent clinical and radiologic follow-up for at least three years after the surgery. Results The mean follow-up period lasted 57 months. To the last follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…In the current study, burst level fusion reached 83.3% at 3 months after surgery and 98.3% at 6 months, which is suggestive of early and excellent fusion. According to the previous anterior surgery study, 13 18 the average fusion time was about 4.5 months. However, they have not clearly mentioned the exact fusion rate during their followup period which made it hard to compare with our results.…”
Section: Discussionmentioning
confidence: 96%
“…In the current study, burst level fusion reached 83.3% at 3 months after surgery and 98.3% at 6 months, which is suggestive of early and excellent fusion. According to the previous anterior surgery study, 13 18 the average fusion time was about 4.5 months. However, they have not clearly mentioned the exact fusion rate during their followup period which made it hard to compare with our results.…”
Section: Discussionmentioning
confidence: 96%
“…A favorable surgical outcome of single-level anterior fusion was reported in patients with thoracolumbar burst fracture in which the cranial endplate is mainly involved and the caudal endplate has no or slight injury. [ 12 , 15 , 21 ] A previous study showed that postoperative correction loss was not significantly different between single-level and two-level anterior fusion surgery in such patients. [ 17 ] Miyakoshi et al .…”
Section: Discussionmentioning
confidence: 99%
“…Anterior approaches can achieve complete removal of the retropulsed bone and soft tissue fragments from the spinal canal under direct visualization without manipulation of the dural tube, as well as anterior reconstruction using plate or rod with bone graft [25]. Theoretically, the anterior approach offers a satisfactory canal decompression and a better chance of neurologic improvement compared to other procedures [25]. However, this approach is surgically challenging and more likely to have complications due to the adjacent chest and abdominal organs as well as major blood vessels [7].…”
Section: Discussionmentioning
confidence: 99%